EXPOSURE TIME AND MONITOR DISTANCE WITH EYE FATIGUE IN EMPLOYEES OF THE REGIONAL OFFICE OF LABOR BPJS SUMBAGUT MEDAN - Husna, Jihaan Hazrati; Salwa, Jihan Maishie; Rifdha, Aliyah; Sinaga, Nur Elviyani; Prasetyo, Rendy; Permata, Marcella; Utami, Tri Niswati (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Workers who use computers in daily activities often experience eye fatigue. Visual disorders caused by computer use can include various complaints, such as: blurred vision, unclear images, double vision, difficulty distinguishing colors, red eyes, eyes that are often sore, frequently itchy, often feeling tense, eyes that easily become sleepy, reduced accommodation ability, and headache symptoms. This research uses qualitative research as a complex description, by studying words, obtaining detailed reports from respondents' perspectives, and investigating experienced situations. The purpose of this research is to determine the relationship between long exposure and monitor distance with employee eye fatigue at the BPJS Ketenagakerjaan Sumbagut Regional Office. Employees working with an 8-hour system per day for 5 working days rarely apply the 20-20-20 method recommended by the Ministry of Health to prevent eye fatigue.